NRICM101 ameliorates SARS-CoV-2–S1-induced pulmonary injury in K18-hACE2 mice model - Wei, Wen-Chi; Tsai, Keng-Chang; Liaw, Chia-Ching; Chiou, Chun-Tang; Tseng, Yu-Hwei; Liao, Geng-You; Lin, Yu-Chi; Chiou, Wen-Fei; Liou, Kuo-Tong; Yu, I-Shing; Shen, Yuh-Chiang; Su, Yi-Chang (Frontiers in Pharmacology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic continues to represent a challenge for public health globally since transmission of different variants of the virus does not seem to be effectively affected by the current treatments and vaccines. During COVID-19 the outbreak in Taiwan, the patients with mild symptoms were improved after the treatment with NRICM101, a traditional Chinese medicine formula developed by our institute. Here, we investigated the effect and mechanism of action of NRICM101 on improval of COVID-19-induced pulmonary injury using S1 subunit of the SARS-CoV-2 spike protein-induced diffuse alveolar damage (DAD) of hACE2 transgenic mice. The S1 protein induced significant pulmonary injury with the hallmarks of DAD (strong exudation, interstitial and intra-alveolar edema, hyaline membranes, abnormal pneumocyte apoptosis, strong leukocyte infiltration, and cytokine production). NRICM101 effectively reduced all of these hallmarks. We then used next-generation sequencing assays to identify 193 genes that were differentially expressed in the S1+NRICM101 group. Of these, three (Ddit4, Ikbke, Tnfaip3) were significantly represented in the top 30 enriched downregulated gene ontology (GO) terms in the S1+NRICM101 group versus the S1+saline group. These terms included the innate immune response, pattern-recognition receptor (PRR), and Toll-like receptor signaling pathways. We found that NRICM101 disrupted the interaction of the spike protein of various SARS-CoV-2 variants with the human ACE2 receptor. It also suppressed the expression of cytokines IL-1β, IL-6, TNF-α, MIP-1β, IP-10, and MIP-1α in alveolar macrophages activated by lipopolysaccharide. We conclude that NRICM101 effectively protects against SARS-CoV-2-S1-induced pulmonary injury via modulation of the innate immune response, pattern-recognition receptor, and Toll-like receptor signaling pathways to ameliorate DAD.